2017
DOI: 10.1111/jpc.13514
|View full text |Cite
|
Sign up to set email alerts
|

Differences in survival outcome for severely injured paediatric trauma by type of trauma centre

Abstract: Children who received definitive care at a PTC had a survival advantage compared to those treated at a Level 1 ATC. Prospectively examining the processes of care for severely injured children may assist in identification of quality and system changes required to ensure optimal trauma care within the health-care system.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
1
12
0
Order By: Relevance
“…This is consistent with the findings of Miyata et al, which showed survival benefits for pediatric trauma patients in high-volume trauma centers in a cohort of over 3700 children with ISS greater than 25 [28]. These results have been confirmed by several studies, underlining the survival benefits of specialized pediatric trauma centers [10,11,29,30]. Interestingly, Brown et al included in-hospital confounders, such as trauma center type, and demonstrated a two-fold increase in survival for treatment in level I compared to level II pediatric trauma centers [8].…”
Section: Discussionsupporting
confidence: 91%
“…This is consistent with the findings of Miyata et al, which showed survival benefits for pediatric trauma patients in high-volume trauma centers in a cohort of over 3700 children with ISS greater than 25 [28]. These results have been confirmed by several studies, underlining the survival benefits of specialized pediatric trauma centers [10,11,29,30]. Interestingly, Brown et al included in-hospital confounders, such as trauma center type, and demonstrated a two-fold increase in survival for treatment in level I compared to level II pediatric trauma centers [8].…”
Section: Discussionsupporting
confidence: 91%
“…89e91 Mature trauma systems have integrated paediatric-specific guidelines, and designated paediatric trauma centres, with an attributable survival benefit for children and adolescents. 90,92 Despite paediatric patients featuring significantly in MCIs, 47,93,94 most research has investigated the disaster preparedness of trauma centres in the adult setting. Paediatric patients have been considered at increased risk of adverse outcomes because of their anatomy and physiology.…”
Section: Post-disaster Recoverymentioning
confidence: 99%
“…In 2010, a retrospective review of 1138 severely injured children using data from the NSW Trauma Registry, children who received definitive treatment at a PTC were between 3 and 6 times more likely to survive than if they were treated at an ATC [3] . A repeat study in 2017 had similar findings [4] . The reasons for the finding of a survival benefit at a PTC were unclear.…”
Section: Introductionmentioning
confidence: 62%